Zadania pedagoga szkolnego i pedagoga specjalnego w świetle przepisów prawa oświatowego i praktyki szkolnej - obszary wspólne i odrębne = The tasks of school counselors and special education counselors in light of educational law and school practice - common and distinct areas - Parys, Katarzyna; Olszewski, Sławomir (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of this text is to present the responsibilities of school counselors and special education counselors in light of educational law and school practice, identify areas of overlap and differentiation, and ultimately formulate recommendations for the effective division of tasks between these specialists. The authors present the evolution of the positions of these specialists, emphasizing that the introduction of the special education counselor position in 2022 was intended to strengthen the support system for students with special educational needs and improve the implementation of inclusive education.
Keywords: pedagog szkolny; pedagog specjalny; edukacja włączająca; wielopoziomowy system wsparcia; school counselor; special education counselor; inclusive education; multi-tiered system of supports